Designing a mobile system of robust noise monitoring of changes in the heart activity - Рзаева, Нармин Эльдар (Eastern-European Journal of Enterprise Technologies, 2015)
Since nowadays the number of cases of heart disease progressively increases, the article presents the algorithms for robust noise monitoring of the changes in the cardiovascular system and the concept of the monitoring system. It is found that the use of the technologies proposed in the article allows a reliable monitoring of changes in the cardiovascular system online. The latter is ensured by the robust noise characteristics of the heart murmurs that are used to make up a plurality of informative signs. The creation of the robust noise monitoring system would minimize the number of unwarranted visits to doctors and, consequently, facilitate their work. The study has also proved that the above purpose is compatible with the use of notebooks and smart phones. We have considered the concept of the heart monitoring system via a laptop and a smart phone. The system can be implemented in two ways: (1) for the mass use––for healthy people who want to control the functioning of their heart, and (2) for patients suffering from cardiovascular diseases. In either case, the system can be: (A) a Lithmann 3200 electronic stethoscope that listens to heart murmurs at regular intervals and sends the information wirelessly to a laptop for its subsequent processing, and (B) a system that does not imply any additional equipment. Listening to the heart murmurs takes place via the microphone of a smart phone with a mode of increased sensitivity of the microphone.